1995
DOI: 10.1037/0022-3514.68.6.1121
|View full text |Cite
|
Sign up to set email alerts
|

Social dating goals in late adolescence: Implications for safer sexual activity.

Abstract: This research examined 2 age-typical goals that adolescents may pursue in social dating (intimacy goals related to open communication and mutual dependence and identity goals related to self-reliance and self-exploration) and the implications of these different goal sets for responsiveness to educational and daily life situations. Education about safer sexual activity that emphasized interpersonal communication skills was more effective in increasing intentions regarding safer sex for adolescents with predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 37 publications
6
106
1
2
Order By: Relevance
“…This multivariate approach extends to interventions to reduce risk or increase selfprotection. Sanderson and Cantor (1995), for example, found that educational interventions regarding use of condoms to promote safer sex that emphasized differing social dating goals (intimacy versus identity) were most effective for those individuals whose goals matched the message.…”
Section: Personal Goals and Risk Perceptionmentioning
confidence: 99%
“…This multivariate approach extends to interventions to reduce risk or increase selfprotection. Sanderson and Cantor (1995), for example, found that educational interventions regarding use of condoms to promote safer sex that emphasized differing social dating goals (intimacy versus identity) were most effective for those individuals whose goals matched the message.…”
Section: Personal Goals and Risk Perceptionmentioning
confidence: 99%
“…In effect, this approach addresses only situations in which one motivation operates at a time. Other research has similarly focused on motives in isolation, either identifying a particular motivational goal as primary for an individual (e.g., Omoto et al, 2000;Sanderson & Cantor, 1995) or measuring several motivations for each individual (e.g., Clary et al, 1998;Omoto & Snyder, 1995), but still separately assessing the effects of individual motivations on outcomes. Another way of stating this distinction is that existing research has explored differences in the overall amount of a given motivation but has not examined another potentially important feature-differences in the number of conceptually distinct motivations one has for an activity.…”
mentioning
confidence: 99%
“…Young adults are encouraged to form monogamous dating relationships and to become self-reliant and independent from their family (Sanderson & Cantor, 1995 After making a long term commitment in an intimate romantic relationship, most Americans choose to cohabit with their romantic partner prior to marriage. Estimates are as high as 70% of all couples cohabitating prior to marriage (Hsueh, Morrison, & Doss, 2009;Rhoades, Stanley, & Markman, 2009).…”
Section: Marriage and Family Relationships In The Us And Egyptmentioning
confidence: 99%